(untitled) (Secretariado Executivo em Revist@, 2018)
Secretariado Executivo em Revist@ Nº 14/2018 ISSN 1809-2802 Acesso: www.upf.br/seer EDITORA Josete Alzira Passamani Stocco Universidade de Passo Fundo – UPF, Rio Grande do Sul, Brasil EDITORA CIENTÍFICA Caroline de Fátima Matiello Vaz Universidade de Passo Fundo – UPF, Rio Grande do Sul, Brasil CONSELHO EDITORIAL Aline Cantarotti, Universidade Estadual de Maringá – UEM, Paraná, Brasil Cibele Barsalini Martins, Universidade Federal de Santa Catarina – UFSC, Santa Catarina, Brasil Cibelle da Silva Santiago, Universidade Federal da Paraíba – UFPB, Paraíba, Brasil Chussy Karlla Souza Antunes, Universidade Federal de Pernambuco – UFPE, Pernambuco, Brasil Daniela Giareta Durante, Universidade Federal do Ceará - UFC, Ceará, Brasil Eduardo César Pereira Souza, Universidade Cruzeiro do Sul – UNICSUL, São Paulo, Brasil Emili Barcellos Martins Santos, City University of Seattle, Seattle, Washington Eliane Wamser, Universidade Regional de Blumenau – FURB, Santa Catarina, Brasil Fernanda Cristina Sanches, Universidade Estadual do Oeste do Paraná – UNIOESTE, Paraná, Brasil Keila Raquel Wenningkamp, Universidade Estadual do Oeste do Paraná – UNIOESTE, Paraná, Brasil Maria do Carmo Assis Todorov, Universidade Nove de Julho – Uninove, São Paulo, Brasil Maria Elisabete Mariano dos Santos, Universidade de Passo Fundo – UPF, Rio Grande do Sul, Brasil Maria Luzitana Conceição dos Santos, Universidade Federal da Paraíba – UFPB, Paraíba, Brasil Raul Vitor Oliveira Paes, Universidade Federal do Pará – UFPA, Pará, Brasil Rodrigo Müller, Universidade Tecnológica Federal do Paraná - UFTPR, Brasil Rosimeri Ferraz Sabino, Universidade Federal de Sergipe - UFS, Sergipe, Brasil